“Sí, otro mundo es posible”: Aportes fundamentales de Chalena Vásquez Rodríguez a la investigación de las artes - Riveros Vásquez, César Camilo (2025)
Noteworthy contributions in Chalena Vasquez's theoretical works on the right to one's own culture and artistic production processes as well as case studies on the Danza de Negritos de El Carmen, the dances of Paucartambo, the Ayacucho carnival, the biography of composer Ranulfo Fuentes and thoughts on light and sound in the work of José María Arguedas.